1990
DOI: 10.1042/cs0790477
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma Histamine Levels in Uraemic Pruritus

Abstract: 1. We determined plasma levels of histamine in uraemic patients and examined their correlation with the presence of pruritus. 2. In 27 patients with chronic renal failure, plasma histamine levels were analysed by radioimmunoassay and were compared with those of 40 healthy adult subjects. The control population showed plasma histamine concentrations of 185 +/- 33 pg/ml, which were significantly lower than those of the patients with renal insufficiency. The highest levels (552 +/- 116 pg of histamine/ml) were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
7

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 5 publications
1
30
1
7
Order By: Relevance
“…Some investigators have found a positive correlation between plasma histamine levels and pruritus [7, 8, 11, 15, 16], but this has not been confirmed by others [5, 30]. In our study, the plasma histamine levels of patients with pruritus were higher than those of nonpruritic patients, but the difference was not statistically significant (p = 0.06).…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…Some investigators have found a positive correlation between plasma histamine levels and pruritus [7, 8, 11, 15, 16], but this has not been confirmed by others [5, 30]. In our study, the plasma histamine levels of patients with pruritus were higher than those of nonpruritic patients, but the difference was not statistically significant (p = 0.06).…”
Section: Discussioncontrasting
confidence: 45%
“…It was reported that plasma histamine levels were increased in uremic patients, mainly in those with pruritus [5, 7, 8, 11, 15, 16, 29, 30]. Some investigators have found a positive correlation between plasma histamine levels and pruritus [7, 8, 11, 15, 16], but this has not been confirmed by others [5, 30].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The complex interplay Fig. 4 Changes in drugs used for pruritus treatment in patients managed at our facility of these multiple factors in hemodialysis patients can result in pruritus that often fails to respond sufficiently to existing treatments, including antihistamines, antiallergy drugs, and steroids [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%